Effects of dexmedetomidine on early postoperative cognitive function and postoperative inflammatory response: a systematic review and network meta-analysis - Huang, Cuifang; Yang, Ruimin; Xie, Xianlong; Dai, Huijun; Pan, Linghui (Frontiers in Neurology, 2024)
Background Dexmedetomidine (DEX) has demonstrated potential as an effective agent for enhancing early postoperative cognitive function. However, there is ongoing debate regarding its optimal dosage and impact on early postoperative inflammatory response. This study aimed to assess and prioritize the effects of varying doses of DEX on early postoperative cognitive function and inflammatory response, in order to identify the most effective intervention dosage. Methods Randomised controlled trials (RCTs) and retrospective cohort studies (RCS) from PubMed, Embase, and Cochrane Library up to January 28, 2024, were included. The Mini-Mental State Examination (MMSE) was utilized to assess the impact of varying doses of DEX on cognitive function during the early postoperative period as the primary outcome, peripheral blood levels of IL-6 and TNF-α were considered as secondary outcomes. Meta-analysis and Bayesian Network Meta-Analysis (NMA) were conducted using R. Funnel plots were generated using Stata 15.0. Results A total of 29 studies involving 2,807 patients and 25 different doses of DEX were included. DEX was given at a loading dose of 0.3–1.0 μg/kg followed by a maintenance dose of 0.1–0.5 μg/kg/h, or at a uniform intraoperative dose of 0.4–0.7 μg/kg/h. Network meta-analysis revealed most doses of DEX were significantly more effective than normal saline (NS) in improving postoperative MMSE scores (on days 1, 3, and 7) and lowering IL-6 and TNF-α levels. Probability results showed that a 1 μg/kg loading dose followed by a 0.6 μg/kg/h maintenance dose was the best dosing regimen for improving MMSE scores on postoperative days 1 (97.3%), 3 (100%), and 7 (99.9%), as well as for reducing postoperative blood IL-6 levels (1.3%). On the other hand, 0.3 μg/kg followed by 0.2 μg/kg/h was the optimal dosing regimen for reducing postoperative blood TNF-α levels (6.6%). Conclusion Compared with NS, intraoperative intravenous DEX improved early postoperative cognitive function and postoperative inflammatory response in patients undergoing elective surgery. In particular, a 1 μg/kg loading dose and a 0.6 μg/kg/h maintenance dose resulted in the best improvement in postoperative MMSE scores and blood IL-6 levels, while a 0.3 μg/kg loading dose followed by a 0.2 μg/kg/h maintenance dose is the optimal regimen for lowering postoperative blood TNF-α levels. Systematic review registration: https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=433932, identifier CRD42023433932.